(untitled) (Comprehensive Journal of Science, 2026)
This study aimed to analyze the practical, professional, psychological, and organizational challenges faced by the medical team at the infertility center in Al-Zawiya, and to demonstrate their impact on professional performance. The importance of the study stems from the sensitivity of work in infertility treatment centers and the accompanying professional and organizational pressures, in addition to the limited number of local studies that have addressed this topic statistically. The study relied on a descriptive analytical approach, and data was collected using a questionnaire designed in light of previous literature and distributed to a random sample of 100 members of the medical team, from which 60 questionnaires were retrieved for statistical analysis. The data were analyzed using SPSS software, relying on descriptive and inferential statistics and a one-sample t-test, after verifying the validity and reliability of the tool. The results of the study showed the existence of statistically significant practical (daily) challenges that affect the performance of the medical team, especially with regard to the clarity of daily tasks, the availability of technical support, and the smooth flow of work within the center. On the other hand, the results did not show any professional, psychological, or social challenges with a statistically significant impact on performance, which is attributed to the cooperative work environment and mutual support among colleagues. The results also showed that organizational and practical factors had a greater impact on performance than individual factors. The study concludes that it is necessary to improve the organizational work environment, enhance technical and administrative support, and develop training and incentive mechanisms, thereby contributing to raising the efficiency of professional performance and the quality of health services provided at the infertility center in Al-Zawiya.